Diosgenin Induces Apoptosis of MCF-7 Cells by Regulating DAXX Subcellular Localization and Activating JNK/p38 Signaling Pathway - Jia WANG; Shilei GAO; Lihan ZHANG; Lu ZHANG; Xu SUN; Huahua LI; Huaimin LIU (Zhongliu Fangzhi Yanjiu)
ObjectiveTo investigate the effect of diosgenin on the proliferation and apoptosis of breast cancer cells and its potential molecular mechanism. MethodsThe breast cancer cell line MCF-7 was treated with low, medium, and high doses of diosgenin, and cell proliferation was detected through the MMT method. Flow cytometry was used to detect cell apoptosis. Nuclear-cytoplasmic-protein separation method was applied to detect the subcellular localization of death associated protein (DAXX). qRT-PCR and Western blot were used to detect the expressions of DAXX and c-Jun N-terminal kinase pathway (JNK)-related proteins. ResultsDiosgenin considerably inhibited the proliferation of MCF-7 cells and promoted cell apoptosis in a concentration-dependent manner. Diosgenin can promote the movement of DAXX from nucleus into the cytoplasm. Diosgenin upregulated the expression of cell surface death receptor (Fas), increased the phosphorylation levels of JNK and mitogen activated protein kinase (p38), and activated the JNK/p38 signaling pathway with concentration dependence. ConclusionDiosgenin inhibits the proliferation and promotes the apoptosis of the breast cancer cell line MCF-7, whose mechanism may be related to the regulation of DAXX subcellular localization and the activation of JNK/p38 signaling pathway.